Identification of bored pile defects utilizing torsional low strain integrity test: Theoretical basis and numerical analysis - Yunpeng Zhang; Hongxuan Ji; Lulu Zhang; M. Hesham El Naggar; Wenbing Wu (Journal of Rock Mechanics and Geotechnical Engineering)
The torsional low strain integrity test (TLSIT), known for its advantages such as a smaller detection blind zone, improved identification of shallowly buried defects, stable phase velocity for signal interpretation, and better adaptability for existing pile testing. However, it lacks a comprehensive understanding of the authentic three-dimensional (3D) strain wave propagation mechanism, particularly wave reflection and transmission at defects. To address this gap, a novel 3D theoretical framework is introduced in this context to model the authentic 3D wave propagation during the TLSIT. The proposed approach is validated by comparing its results with those obtained from 3D finite element method (FEM) simulations and simplified 1D (one-dimensional) and 3D analytical solutions. Additionally, a parametric study is conducted to enhance insights into the formation mechanism of high-frequency interference observed during the TLSIT. Finally, a defect identification study is performed to provide guidance for interpreting the wave spectrum in terms of defect characteristics.